Personalised learning as repressive tolerance: a comparative ethnographic analysis from research in three Swedish schools. Issue 3 (1st September 2016) - Dovemark, Marianne; Johansson, Monica
ABSTRACT: The idea of personalised learning is built upon a liberal tradition that values tolerance in enabling the process of human autonomy. In this article, we elaborate on this notion, its theoretical base and effects on the learning conditions of upper secondary school students. We draw upon data from three different studies of the Swedish upper secondary school. The aim of the article is to elaborate on values that are implemented and how these values affect how the notion of tolerance can be used as a tool to explore and explain the idea of personalised learning. For the purpose of analysis, we use parts of Kyle Moore and Walker's [2011. "Tolerance. A Concept Analysis." The Journal of Theory Constructing & Testing 5 (2): 48–52] work. Our analysis shows that personalised learning was legitimised in our studied settings, but in its extension it did not benefit and challenge the ongoing learning and development of the students. In fact, tolerance appeared repressive and confirmed status quo.